2017
DOI: 10.1111/joor.12504
|View full text |Cite
|
Sign up to set email alerts
|

Association between occlusal force distribution in implant overdenture prostheses and residual ridge resorption

Abstract: This study aimed to investigate residual ridge resorption (RRR) of anterior and posterior maxillary and mandibular edentulous ridges, in patients treated with mandibular implant overdentures (IOD) and compare with conventional complete denture (CD) wearers, and to determine at each location, the association of RRR with the occlusal forces distribution and other patients' variables. The anterior and posterior RRR of IOD (six males, 17 females) and CD (12 males, 11 females) groups were determined using baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
0
23
0
2
Order By: Relevance
“…Several studies showed that using two or four dental implants retained overdenture improve the function of the denture 1,2,40,41 . From our study, we are comparing the occlusal analysis before and after using mini‐dental implants to retain the lower complete dentures.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies showed that using two or four dental implants retained overdenture improve the function of the denture 1,2,40,41 . From our study, we are comparing the occlusal analysis before and after using mini‐dental implants to retain the lower complete dentures.…”
Section: Discussionmentioning
confidence: 95%
“…It also aided in increasing the bone density and its stability around the implants preventing uneven forces and bone Resorption reaction in certain areas. (33,34) Bite force is an important variable to investigate proper oral function which is related to occlusal factor, dentition, dentures, and treatment with implants, orthognathic surgery, temporomandibular disorders and neuromuscular changes. (35) Regarding to the results of load distribution of this study revealed that the Overdenture with balanced occlusion, such as posterior balance force direct the force to the target area, and most of teeth contributing to occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…That may attribute to the stability and retention in Overdenture retained by locator attachment superior than those retained by ball and socket due to the dual retention action of the locators attachments. (33)(34)(35) The Biting force and the number of functional teeth are directly related to the masticatory function as the measuring maximum bite force is attributed to the force quantity that elevator muscles can performed .The results of this study revealed that the maximum biting force was recorded in both groups while in group I treated by Mandibular over denture retained by locator attachment recorded more than those treated with Mandibular over denture retained by ball attachment (group II) However, this increase was not statistically significant that may be attribute to the nature of the locator attachment with parallel walls and flat occlusal top that may be increase retention and make limitation of the movement which may decrease the resilience of the attachment especially when compared with the ball attachment which considered the resilient attachment allow the universal rotation . Also the double retentive surface area "Dual retention" ensuring long-lasting retention life and allow increase biting and muscle force .…”
Section: Discussionmentioning
confidence: 99%
“…[1] The number of dentures an individual has worn does not seem to influence the amount of resorption [1]. However, excessive forces in concentrated areas speed resorption in that area and dentures that provide evenly distributed force may result in slower resorption [2]. Osteoporosis does not directly have an impact on the residual ridge height as it effects bone mass and not structure [3].…”
Section: Introductionmentioning
confidence: 99%